Impact of Mud Contamination on Performance of Granite-Based Geopolymers - Khalili, Pouya (University of Stavanger, 2024)
Ensuring zonal isolation and long-term integrity are fundamental in primary cementing in the well construction phase. Successful cementing can be compromised by various factors, including contamination with drilling fluid. Given that drilling fluid is present in the wellbore before cementitious material is pumped, it is possible that mixing between these fluids takes place downhole, affecting the properties of the barrier material. To mitigate this, spacer fluid is normally pumped in front of the cement slurry to minimize the commingling of drilling fluid and improve bonding. Geopolymer is seen as a potential replacement for Ordinary Portland Cement. Prior to its use in well construction and abandonment, the impact of drilling fluid contamination on geopolymer performance must be assessed. In this study, the impact of drilling fluid contamination on the liquid-state and solid-state properties of granite-based geopolymer, developed at the University of Stavanger (UiS), was investigated at elevated temperatures (50 ℃ BHCT/70 ℃ BHST). Oil-based drilling fluid (OBDF) and water-based drilling fluid (WBDF) were formulated in the lab with representative mix designs for the contamination study. Additionally, a spacer fluid tailored for geopolymer was designed to minimize contamination by drilling fluid. The thesis presented here is the result of the SafeRock Project, a collaboration between UiS and operators aimed to meet industry standards with geopolymeric materials. The PhD dissertation is structured into two primary sections: the first section outlines the research project, while the second section consists of appended papers comprising detailed scientific findings. The outcomes of this research have been published across five scientific papers: three in journals, one in a peer-reviewed conference, and one in an SPE conference. These papers are included as appendices and are labeled using Roman numerals. Throughout this thesis, the same numerals are utilized for the sake of referring. Paper I: Geopolymer slurry was ...